Study of Synthesis Mechanism and Electrochemical Performance of LiTi2(PO4)3 - Zhu, Wei; Niu, Feng-Guang; Yang, Ya-Ping; Wang, Zuo-Long; Yao, Jing; Wang, Zhang-Gan (Asian Journal of Chemistry, 2014)
LiTi2(PO4)3/C was synthesized by high-temperature solid-state method. The microstructure, morphology of the samples were characterized and investigated by X-ray diffraction and its electrochemical properties were characterized in an organic and aqueous electrolyte. Galvan static charge-discharge cycling of the resulting lithium titanium phosphate showed an initial discharge capacity of 142.7 mAh/g and quite good capacity retention during cycling, 97 % after 50 cycles and 90.17 % after 50 cycles at a 5 C cycling rate in an organic electrolyte. Choosing LiFePO4/2M, Li2SO4/LiTi2(PO4)3/C and LiCoO2/2 mol/L, Li2SO4/LiTi2(PO4)3/C as the aqueous solution battery system, test LiTi2(PO4)3/C/Galvan static charge-discharge performance. The result showed an initial discharge capacity of 69.4 mAh/g and 59.1 mAh/g respectively and their voltage platform is 0.9 V and 1.5 V at a 4 C cycling rate. All of those two aqueous battery systems have a good cycle performance.